Genome-Wide DNA Methylation Analysis during Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells. (10th September 2018) - Cao, Yangyang; Yang, Haoqing; Jin, Luyuan; Du, Juan; Fan, Zhipeng
Abstract : Bone marrow mesenchymal stem cells (BMSCs) nowadays are regarded as promising candidates in cell-based therapy for the regeneration of damaged bone tissues that are either incurable or intractable due to the insufficiency of current therapies. Recent studies suggest that BMSCs differentiate into osteoblasts, and that this differentiation is regulated by some specific patterns of epigenetic modifications, such as DNA methylation. However, the potential role of DNA methylation modification in BMSC osteogenic differentiation is unclear. In this study, we performed a genome-wide study of DNA methylation between the noninduced and induced osteogenic differentiation of BMSCs at day 7. We found that the majority of cytosines in a CpG context were methylated in induced BMSCs. Our results also revealed that, along with the induced osteogenic differentiation in BMSCs, the average genomic methylation levels and CpG methylation in transcriptional factor regions (TFs) were increased, the CpG methylation level of various genomic elements was mainly in the medium-high methylation section, and CpG methylation levels in the repeat element had highly methylated levels. The GO analysis of differentially methylated region- (DMR-) associated genes (DMGs) showed that GO terms, including cytoskeletal protein binding (included in Molecular Function GO terms), skeletal development (included in Biological Process GO terms), mesenchymal cell differentiation (included in Biological Process GO terms), and stem cell differentiation (included in Biological Process), were enriched in the hypermethylated DMGs. Then, the KEGG analysis results showed that the WNT pathway, inositol phosphate metabolism pathway, and cocaine addiction pathway were more correlative with the DMRs during the induced osteogenic differentiation in BMSCs. In conclusion, this study revealed the difference of methylated levels during the noninduced and induced osteogenic differentiation of BMSCs and provided useful information for future works to characterize the important function of epigenetic mechanisms on BMSCs' differentiation.